2008
DOI: 10.2119/2007-00050.yuan
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Epigallocatechin Gallate on Colon Preneoplastic Lesions Induced by 2-Amino-3-Methylimidazo(4,5-f)Quinoline in Mice

Abstract: Epigallocatechin gallate (EGCG), a key active ingredient in green tea, has multiple anticarcinogenic effects. The aim of the present study was to investigate if EGCG could prevent the formation of colon aberrant crypt foci (ACF) induced by 2-amino-3-methylimidazo[4,5-f ]quinoline (IQ) and to explore possible mechanisms for resultant effects. Sixty male BALB/cA nude, immunodeficient mice were divided into six groups including a normal unexposed control, mice induced with IQ alone, three groups treated with vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…It is possible that the induction of these antioxidant defenses occurs downstream from the transcriptional activation of NF-E2-related factor-2 (Nrf2) via its interaction with the antioxidant-response element (ARE) [38]. Indeed, EGCG has been shown to increase Nrf2 nuclear translocation and ARE transcriptional activity in vitro [36] and up-regulate Nrf2 protein expression in a mouse model [39]. These GTE-mediated antioxidant activities are important because membrane peroxidation induces cellular damage and activates NFκB-mediated responses that induce proinflammatory cytokine expression including TNF-α [3], which contribute to NAFLD [40].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the induction of these antioxidant defenses occurs downstream from the transcriptional activation of NF-E2-related factor-2 (Nrf2) via its interaction with the antioxidant-response element (ARE) [38]. Indeed, EGCG has been shown to increase Nrf2 nuclear translocation and ARE transcriptional activity in vitro [36] and up-regulate Nrf2 protein expression in a mouse model [39]. These GTE-mediated antioxidant activities are important because membrane peroxidation induces cellular damage and activates NFκB-mediated responses that induce proinflammatory cytokine expression including TNF-α [3], which contribute to NAFLD [40].…”
Section: Discussionmentioning
confidence: 99%
“…(nuclear factor E2-related factor 2-uridine 5 0 -diphosphate glucuronosyltransferase, a phase II metabolism) signalling pathway, among others Yuan et al, 2008). Esterification of EGCG with fatty acids employed in this study might have led to improved lipophilicity and membrane affinity (data shown in , 2012, and presumably enhanced absorption through the intestine.…”
Section: Inhibition Of Aom-induced Acf In Mouse Colonmentioning
confidence: 85%
“…Both hereditary and environmental factors (through ingestion of genotoxins and carcinogens in alimentation) contribute to the development of CRC (Yuan, Li, & Yang, 2008). The pathogenesis of CRC involves sequential and multistep progression of epithelial cells initiated to a cancerous state with defined precancerous intermediaries (Raju, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Intraperitoneal administration of EGCG, at a dose equivalent to four cups of 2% tea for 15 days, elevated the levels of GST, GPx, SOD and catalase in mouse liver, and reduced lipid peroxidation and cell proliferation during the dimethylbenz[a]anthracene (DMBA)-initiated and 12-O-tetradecanoylphorbol-13-acetate (TPA)-promoted mouse skin carcinogenesis (Saha and Das 2002). EGCG, given by gavage, significantly decreased 2-amino-3-methylimidazo[4,5-f]quinoline-induced atypical hyperplasia, the number of aberrant crypt foci and adenocarcinoma formation by activating Nrf2 and upregulating UGT1A10 in mouse colon (Yuan et al 2008). The compound also enhanced the mRNA expression of GCL and GSTp, and the nuclear translocation and the ARE binding of Nrf2 in human mammary epithelial cells .…”
Section: Nrf2mentioning
confidence: 96%